A phosphorus-free degreasing agent before painting for new energy vehicle body panels

By introducing organic alkali, anti-rust agent, corrosion inhibitor, complexing agent and stabilizer into the phosphorus-free degreasing agent, the corrosion and silicate stability of cold-rolled plates in the multi-metal mixed line coating of new energy vehicles has been solved, and better paint film adhesion and appearance quality have been achieved.

CN119753698APending Publication Date: 2025-04-04NANJING KERUN LUBRICANTS +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411983380.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing phosphorus-free degreasing agents are difficult to effectively inhibit the corrosion of the cold-rolled plates in the multi-metal mixed line coating of new energy vehicles, and the stability of silicates is poor, affecting the adhesion and appearance of the paint film.

Method used

The phosphorus-free pre-coating degreasing agent composed of 15-20% organic alkali, 3-4% rust preventing agent, 5-15% corrosion inhibitor, 2-5% complexing agent, 0.2-2% stabilizer, 4-10% surfactant and deionized water is used to inhibit corrosion and improve the adhesion of paint film by reducing conductivity, improving the tolerance of zinc-aluminum ions and the stability of silicates.

Benefits of technology

It effectively suppresses the corrosion of the cold-rolled plate in the multi-metal mixed wire, improves the stability and service life of the degreasing agent, and significantly improves the adhesion and appearance quality of the paint film after cathode electrophoresis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753698A_ABST
    Figure CN119753698A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphorus-free degreasing agent before painting for a new energy vehicle body sheet, which is composed of the following components by mass fraction: 15-20% organic base, 3-4% rust inhibitor, 5-15% corrosion inhibitor, 2-5% complexing agent, 0.2-2% stabilizer, 4-10% surfactant and deionized water balance. The degreasing agent of the invention has no corrosion appearance during the multi-metal mixed line painting process of new energy vehicles, and the tank liquid has strong stability, and can also meet the adhesion standard of the electrophoretic paint film after cathode electrophoresis and good appearance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a phosphorus-free pre-painting degreasing agent for new energy vehicle body panels. Background Art

[0002] As global energy and environmental issues become increasingly prominent, energy conservation and emission reduction of automobiles have become an important development direction of the automobile industry. Compared with fuel vehicles, new energy vehicles driven by electric motors have great emission reduction advantages due to different energy forms, and have become an important trend in the transformation of the future automobile industry. However, the weight of lithium batteries matching new energy vehicles currently accounts for a large proportion of the entire vehicle. Due to the requirements of maneuverability and endurance, the entire vehicle must be designed to reduce weight, so aluminum alloy plates are often used in the body of new energy vehicles. However, the cost of aluminum alloys is high, so cold-rolled plates and galvanized plates are mixed when the whole vehicle plate is used, which creates the need for co-line coating of multiple complex plates for new energy vehicles.

[0003] Existing phosphorus-free degreasing agent products mainly use silicates as corrosion inhibitors, and enhance the corrosion inhibition ability of aluminum alloys by lowering the pH value of the degreasing agent bath (9.0-10.0). The aluminum plates commonly used in new energy vehicles are 5-series or 6-series aluminum alloys. In actual vehicle bodies, since aluminum alloys may be coupled with cold-rolled plates, and the surface of 5-series or 6-series aluminum alloys is a dense aluminum oxide film, the electrode potential is higher than that of cold-rolled steel plates, and there is a huge potential difference with cold-rolled plates. At this time, the corrosion rate of cold-rolled steel plates as anodes increases, making cold-rolled plates more susceptible to rust, thus affecting the appearance and adhesion performance after painting. Moreover, when working under this pH value, the stability of silicates is poor, and they are prone to hydrolysis and polymerization to form a polymer form of silicates, resulting in a decrease in corrosion inhibition performance. On the other hand, existing phosphorus-free degreasing agent products have low tolerance to dissolved zinc and aluminum ions. After long-term use, aluminum silicate and aluminum hydroxide will be formed in the bath liquid. Aluminum silicate and aluminum hydroxide sols are easily adsorbed on the surface of the plate and are difficult to remove by water washing, which seriously affects the adhesion performance and electrophoretic appearance of the paint film on the surface of the plate after cathodic electrophoresis. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a degreaser suitable for multi-metal mixed line coating of new energy vehicles. On the one hand, the degreaser inhibits the generation of corrosion current by greatly reducing the conductivity of the degreaser tank liquid, thereby effectively inhibiting the corrosion of mixed-line metal plates with a potential difference; on the other hand, the degreaser can effectively improve the tolerance of zinc and aluminum ions in the degreaser tank liquid (no excessive zinc and aluminum ions will accumulate in the tank liquid after longer use) and the long-term stability of silicates (no opaque gel precipitation of silicate polymerization is observed after the degreaser is left to stand for more than one month), and by preventing the generation of aluminum silicate and aluminum hydroxide, the film appearance and adhesion of the electrophoretic paint film after cathodic electrophoresis are greatly improved.

[0005] Technical solution: The phosphorus-free pre-painting degreasing agent of the present invention is composed of the following components in mass fraction: 15-20% organic base, 3-4% rust inhibitor, 5-15% corrosion inhibitor, 2-5% complexing agent, 0.2-2% stabilizer, 4-10% surfactant and the balance of deionized water.

[0006] Wherein, the organic base is at least one of diethanolamine, N-methyldiethanolamine, diglycolamine, triethanolamine, dicyclohexylamine or isopropanolamine.

[0007] Among them, the mass concentration of the phosphorus-free pre-painting degreasing agent working liquid is 3-3.5%, and the pH of the working liquid is 10-10.5. When the pH is greater than 10.5, the corrosion to the aluminum alloy is too large during the initial tank preparation. When the pH is less than 10.0, the pH buffering capacity is insufficient. Under actual spraying conditions, it is easy to absorb carbon dioxide in the air and the pH value will drop below 10.0, causing rust on the cold-rolled steel plate.

[0008] Wherein, the rust inhibitor is at least one of potassium metaborate, borax or boric acid monoethanolamine ester. If its content is low, the rust prevention ability of the cold-rolled steel sheet is insufficient, and if its content is high, the adhesion of the sheet after cathode electrophoresis is too large. Boron substances form a protective film by adsorbing the cold-rolled sheet, slowing down the oxidation rate of iron and zinc to prevent rust, but the boron substances themselves are relatively loose and have no binding force with the paint film, and rinsing is difficult. Excessive use will result in incomplete rinsing of the subsequent water washing, and the adhesion of the paint film after cathode electrophoresis will decrease.

[0009] Wherein, the corrosion inhibitor is sodium metasilicate and / or potassium metasilicate.

[0010] The modulus of the corrosion inhibitor is 2.8 to 3.4. The corresponding modulus can play a role in film-forming corrosion inhibition of silicon-oxygen polymers. The larger the modulus, the easier it is to form a polymer structure of silicon hydroxyl groups, making the film thicker and denser. However, if the modulus is too high, the proportion of polymers will be too high and the water solubility will be too poor, resulting in stability problems of the system.

[0011] Wherein, the complexing agent is at least two of sodium citrate, sodium glucoheptonic acid, disodium ethylenediaminetetraacetic acid, sodium polyaspartate, sodium polyacrylate or maleic anhydride-acrylic acid copolymer; wherein, the molecular weight of the polymer substance is 5000-8000. If the content is low, the complexing and dispersing power of zinc and aluminum ions is insufficient, and if the content is high, the cloud point temperature in the surfactant degreaser tank liquid will be reduced, thereby reducing the degreasing effect (the basic property of non-ionic surfactants is that they are dissolved at the cloud point temperature in the aqueous solution, and will precipitate into a dispersion above the cloud point temperature. In order to obtain the best cleaning performance, the cleaning temperature should be near the cloud point temperature of the active agent. When the polymer is introduced, the cloud point temperature of the non-ionic surfactant will be reduced, so that the active agent at the original cleaning temperature is in a precipitation state, thereby greatly reducing the cleaning power of the degreaser and easily causing residue), and it is more likely to cause water flow marks to affect the appearance of cathode electrophoresis.

[0012] The stabilizer is one of KH-540, KH-550, KH-602 or KH-792. If the content is low, the stability of silicate is insufficient, and if the content is high, the stabilizer is easy to polymerize and fail. The stabilizer can effectively inhibit the hydrolysis and polymerization of silicate in the system.

[0013] Wherein, the surfactant is at least two of isomeric alcohol polyoxyethylene ether, linear alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene polyoxypropylene ether, butyl-terminated fatty alcohol polyoxyethylene ether, fatty acid methyl ester polyoxyethylene ether or alkylamine.

[0014] Wherein, the deionized water satisfies the conductivity of less than 10 μS / cm.

[0015] The present invention introduces a corrosion inhibitor into the degreasing agent, and the pH value of the bath solution can be maintained above 10.0 through a stronger pH buffering capacity, thereby effectively inhibiting the rusting problem of cold-rolled plates in a multi-metal mixed line; by introducing a silicate stabilizer and a complexing agent, the long-term stability of the degreasing agent can be better maintained, ensuring that its corrosion inhibition performance is not affected, thereby extending the service life of the degreasing agent; at the same time, by introducing a complexing agent, the complexing ability of zinc and aluminum ions is enhanced, and the amount of aluminum sol formed is greatly reduced to improve the adhesion performance of the electrophoretic paint film after cathode electrophoresis of galvanized and cold-rolled plates.

[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the degreasing agent of the present invention has no corrosion appearance during the multi-metal mixed line coating process of new energy vehicles, and the tank liquid has strong stability, which can effectively overcome the problem in the prior art that opaque gel precipitation of silicate polymerization can be observed after the degreasing agent is left to stand for 1 to 2 weeks, and the degreasing agent of the present invention can also meet the adhesion standards of the electrophoretic paint film after cathode electrophoresis and have a good appearance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1This is the appearance of the iron-aluminum-zinc coupling plate after cleaning with the degreasing agent of Comparative Example 1;

[0018] Figure 2 This is the appearance of the iron-aluminum coupling plate after cleaning with the degreasing agent of Comparative Example 1;

[0019] Figure 3 This is an appearance diagram of the iron-aluminum-zinc coupling plate after being cleaned with the degreasing agent of Example 1;

[0020] Figure 4 This is the appearance of the iron-aluminum coupling plate after being cleaned with the degreasing agent of Example 1;

[0021] Figure 5 This is an appearance diagram of the iron-aluminum-zinc coupling plate after being cleaned with the degreasing agent of Example 2;

[0022] Figure 6 This is the appearance of the iron-aluminum coupling plate after being cleaned with the degreasing agent of Example 2;

[0023] Figure 7 This is a picture of the adhesion performance of the corresponding paint film on the iron-aluminum-zinc mixed material treated with the degreasing agent in Example 1 after one month of use;

[0024] Figure 8 This is a picture of the adhesion performance of the corresponding paint film on the iron-aluminum-zinc mixed material treated with the degreasing agent in Example 2 after one month of use;

[0025] Fig. 9 This is a picture of the adhesion performance of the corresponding paint film on the iron-aluminum-zinc mixed material treated with the degreasing agent in comparative example 1 after one month of use;

[0026] Fig.10 This is a picture of the adhesion performance of the corresponding paint film on the iron-aluminum-zinc mixed material treated with the degreasing agent in comparative example 2 after one month of use;

[0027] Fig.11 This is a picture of the adhesion performance of the corresponding paint film on the iron-aluminum-zinc mixed material treated with the degreasing agent in comparative example 3 after one month of use;

[0028] Fig.12 This is a picture of the adhesion performance of the corresponding paint film on the iron-aluminum-zinc mixed material treated with the degreasing agent of comparative example 4 after one month of use;

[0029] Fig.13 This is a picture of the adhesion performance of the corresponding paint film on the iron-aluminum-zinc mixed material treated with the degreasing agent in comparative example 5 after one month of use. DETAILED DESCRIPTION

[0030] Example 1

[0031] The phosphorus-free degreasing agent before painting is composed of the following components in mass fraction: 5% diethanolamine, 10% triethanolamine, 3% potassium metaborate, 5% potassium metasilicate (modulus is 2.8), 1% sodium glucoheptonic acid, 1% sodium polyacrylate (molecular weight is 5000), 0.2% KH-550, 2% isomeric alcohol polyoxyethylene ether, 2% fatty alcohol polyoxyethylene polyoxypropylene ether and the balance is deionized water.

[0032] The phosphorus-free degreasing agent before painting of Example 1 is prepared by the following method, specifically: the formula amounts of diethanolamine, triethanolamine, potassium metaborate, sodium glucoheptonic acid, sodium polyacrylate, isomeric alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene polyoxypropylene ether and deionized water are mixed evenly, and then the formula amounts of potassium metasilicate and KH-550 are added thereto, and the degreasing agent is obtained after mixing.

[0033] The phosphorus-free pre-painting degreasing agent of Example 1 was prepared into a 3 wt. % working solution, and 3 g of the degreasing agent was mixed with 97 g of deionized water to obtain a 3 wt. % working solution; the pH of the working solution was 10.3.

[0034] Example 2

[0035] The phosphorus-free degreasing agent before painting is composed of the following components in mass fraction: 20% N-methyldiethanolamine, 4% borax, 15% sodium metasilicate (modulus is 3.4), 2% sodium citrate, 3% maleic anhydride-acrylic acid copolymer (molecular weight is 8000), 2.0% KH-792, 5% butyl-terminated fatty alcohol polyoxyethylene ether, 5% octadecylamine and the balance of deionized water.

[0036] The preparation method of the phosphorus-free pre-painting degreasing agent of Example 2 is the same as that of Example 1.

[0037] The phosphorus-free pre-painting degreasing agent of Example 2 was prepared into a 3 wt. % working solution, and 3 g of the degreasing agent was mixed with 97 g of deionized water to obtain a 3 wt. % working solution; the pH of the working solution was 10.5.

[0038] Comparative Example 1: A commercially available phosphorus-free pre-painting degreasing agent

[0039] The degreasing agent of comparative example 1 was diluted with deionized water to a working solution with a mass concentration of 3%, and heated to 50° C. for use as a degreasing agent tank solution. At this time, the pH of the working solution was 9.5.

[0040] Comparative Example 2

[0041] Compared with Example 1, the only difference in Comparative Example 2 is that inorganic base is used to replace organic base (potassium hydroxide and sodium bicarbonate are used to replace diethanolamine and triethanolamine). It is prepared into a 3wt.% working solution with a pH of 11.5.

[0042] Comparative Example 3

[0043] Compared with Example 1, the only difference of Comparative Example 3 is that it does not contain a complexing agent. It is prepared into a 3 wt.% working solution, and the pH of the working solution is 10.3.

[0044] Comparative Example 4

[0045] Compared with Example 1, the only difference in Comparative Example 4 is that EDTA is used as the complexing agent, which is prepared into a 3 wt. % working solution with a pH of 10.5.

[0046] Comparative Example 5

[0047] Compared with Example 1, the only difference of Comparative Example 5 is that it does not contain a stabilizer. It is prepared into a 3 wt.% working solution, and the pH of the working solution is 10.3.

[0048] Plate selection: HC180YD+Z (produced by Baosteel) with a specification of 50mm×70mm×0.8mm was used as a galvanized plate sample, DC06 (produced by Wuhan Iron and Steel) with a specification of 50mm×70mm×0.8mm was used as a cold-rolled plate sample, and AA6014 (Nolibes) with a specification of 50mm×70mm×0.8mm was used. Galvanized rivets were used to connect dissimilar metals to create coupling conditions on site.

[0049] The above-mentioned plates were respectively subjected to iron-aluminum-zinc coupling and iron-aluminum coupling; three iron-aluminum-zinc coupling plates were respectively placed in the degreasing agent working solution of Examples 1-2 and Comparative Example 1, and were fully immersed at 50°C for 10 minutes before being taken out; three iron-aluminum coupling plates were respectively placed in the degreasing agent working solution of Examples 1-2 and Comparative Example 1, and were fully immersed at 50°C for 10 minutes before being taken out, and the corrosion state of the plate surface after degreasing was observed. The results are as follows Figures 1 to 6 As shown, after being treated with the degreasing agent working solution of comparative example 1, the iron of the iron-aluminum coupling plate was corroded, and the galvanized plate of the tri-metal (iron-aluminum-zinc) coupling plate was corroded with white spots; after being treated with the degreasing agent working solution of embodiments 1 to 2, neither the iron-aluminum coupling plate nor the tri-metal coupling plate had the problem of corrosion and poor appearance.

[0050] After using the degreaser bath solution of Examples 1 to 2 and Comparative Examples 1 to 5 for one month, the iron-aluminum-zinc mixed material was treated at the same time. Seven pieces of the iron-aluminum-zinc mixed material were placed in the degreaser working solution of Examples 1 to 2 and Comparative Examples 1 to 5 respectively, and fully immersed at 50°C for 10 minutes before being taken out to observe the corrosion state of the surface of the board after degreasing. Combined with the two adhesion test standards of GB / T9286-2021 paint and varnish scratch test and GB / T 1732-2020 paint film impact resistance determination method, 100 scratches were made on the surface of the board and then an impact test was performed on the 100 grid positions to examine the damage state of the paint film at the impact position. Figures 7 to 13By comparison, it can be seen that Examples 1 to 2 (all of which are galvanized sheets) have obvious advantages over Comparative Examples 1 to 5 in terms of paint film adhesion (damaged area).

Claims

1. A phosphorus-free degreasing agent before painting for new energy vehicle body panels, characterized in that: The invention is composed of the following components in mass fractions: 15-20% organic base, 3-4% rust inhibitor, 5-15% corrosion inhibitor, 2-5% complexing agent, 0.2-2% stabilizer, 4-10% surfactant and the balance of deionized water.

2. The phosphorus-free degreasing agent before painting according to claim 1, characterized in that: The organic base is at least one of diethanolamine, N-methyldiethanolamine, diglycolamine, triethanolamine, dicyclohexylamine or isopropanolamine.

3. The phosphorus-free degreasing agent before painting according to claim 1, characterized in that: The mass concentration of the phosphorus-free pre-painting degreasing agent working liquid is 3-3.5%, and the pH of the working liquid is 10-10.

5.

4. The phosphorus-free degreasing agent before painting according to claim 1, characterized in that: The rust inhibitor is at least one of potassium metaborate, borax or boric acid monoethanolamine ester.

5. The phosphorus-free degreasing agent before painting according to claim 1, characterized in that: The corrosion inhibitor is sodium metasilicate and / or potassium metasilicate.

6. The phosphorus-free degreasing agent before painting according to claim 5, characterized in that: The modulus of the corrosion inhibitor is 2.8 to 3.

4.

7. The phosphorus-free degreasing agent before painting according to claim 1, characterized in that: The complexing agent is at least two of sodium citrate, sodium glucoheptonate, sodium polyaspartate, sodium polyacrylate or maleic anhydride-acrylic acid copolymer.

8. The phosphorus-free degreasing agent before painting according to claim 7, characterized in that: The molecular weight of polymer substances is 5000-8000.

9. The phosphorus-free degreasing agent before painting according to claim 1, characterized in that: The stabilizer is one of KH-540, KH-550, KH-602 or KH-792.

10. The phosphorus-free degreasing agent before painting according to claim 1, characterized in that: The surfactant is at least two of isomeric alcohol polyoxyethylene ethers, linear alcohol polyoxyethylene ethers, fatty alcohol polyoxyethylene polyoxypropylene ethers, butyl-terminated fatty alcohol polyoxyethylene ethers, fatty acid methyl ester polyoxyethylene ethers or alkylamines.